Boron deficiency in maize - Sittichai Lordkaew (2018)
Boron (B) deficiency depresses wheat, barley and triticale yield through male sterility. On the basis of field responses to B fertilization, maize (Zea mays L.) is affected by B deficiency in five continents. In a series of sand culture trials with maize subject to B0 (nil added B) and B20 (20 μM added B) treatments, we described how B deficiency depressed maize grain yield while showing an imperceptible effect on vegetative dry weight. With manual application of pollen to the silk of each plant, B0 plants produced 0.4 grain ear-1compared with 410 grains ear-1in B20 plants. Symptoms of B deficiency was observed only in B0 plants, which exhibited symptoms of narrow white to transparent lengthwise streaks on leaves, multiple but small and abnormal ears with very short silk, small tassels with some branches emerging dead, and small, shrivelled anthers devoid of pollen. Tassels, silk and pollen of B0 plants contained only 3-4 mg B kg-1DW compared with twice or more B in these reproductive tissues in B20 plants. A cross-fertilization experiment showed that, although the tassels and pollen were more affected, the silk was more sensitive to B deficiency. Pollen from B20 plants applied to B0 silk produced almost no grains, while pollen from B0 on B20 silk increased the number of grains to 37% of the 452 grains plant-1produced from B20 pollen on B20 silk. Therefore, the silk of the first ear may be targeted for precise diagnosis of B status at maize reproduction, for timely correction by foliar B application, and even for B-efficient genotype selection. © 2010 Springer Science+Business Media B.V.